Implications of a Lower Capital Gains Tax Rate in the United States. (IMF Working Papers; Working Paper ;, 1989)
This paper reviews the literature on the revenue implications of a lower capital gains tax rate in the United States. The existing empirical research indicates that the timing of realizations is sensitive to tax changes but is inconclusive on the long-run revenue implications. No study claims that tax revenues would increase very much on a permanent basis. The paper concludes that other aspects of a lower capital gains tax rate deserves more attention, in particular its impact on resource allocation and tax arbitrage.